The Impact of Carbon Tax Implementation on Indonesia's State Budget Revenue Efforts for Sustainable Economic Growth: Revenue Potential, Challenges, and Policy Solutions - Tiara; Salma Isnaeni; Sakti, Fajar Tri (Department of Public Administration, 2025)
The increasing need for state financing and Indonesia's commitment to reducing greenhouse gas emissions require the presence of fiscal instruments capable of supporting economic and environmental sustainability. The carbon tax is a strategic policy because it functions as an emissions control tool and a new source of revenue for the State Budget (APBN). This study aims to analyze the potential state revenue from the implementation of the carbon tax, identify challenges, and formulate optimal policy solutions. The research method used is a qualitative approach through literature study utilizing secondary data. The results show that the carbon tax has significant potential to expand the tax base and increase state revenue, particularly from the high-emission energy sector, as well as encourage changes in consumption and production behavior towards a low-carbon economy. However, the implementation of the carbon tax in Indonesia still faces challenges. The policy implications of this study emphasize the importance of strengthening public outreach, developing an integrated and transparent MRV system, and improving institutional coordination so that the carbon tax can be optimized as a sustainable fiscal and environmental instrument.